EFFECT OF PH PARAMETER ON THE STRUCTURAL PROPERTIES OF THE COMPOUND MG(OH)2 AND ZNO-MG(OH)2 NANO/MICRO PARTICLES PREPARED BY A HYDROTHERMAL ROUTE AND ITS SUITABILITY FOR USE AS AN FIRE RESISTANCE (European Science Methodical Journal, 2025)
The micro- and nanostructures of the product (Magnesium hydroxide -Mg(OH)2), and a composite of ZnO-Mg(OH) as a comparison have been synthesized by hydrothermal method. The structural investigations by XRd results confirmed the formation of hexagonal crystal structure of the products Mg(OH)2 with variable crystalline sizes according to PH Values of Solution. Surface morphology by SEM results are consist of a microstructure Mg(OH)2 and also nanostructure with assortments of shapes as well sizes with transformation of PH values with an aggregations, and a lowest aggregations with ZnO-Mg(OH)2 composites as comparison. FTIR results confirmed that synthesized products are crystallized and the peaks are the Mg-OH and O-H band. UV results found that the energy gap are changed by changing the particle size of product and increasing as it is decreased and adding ZnO to the hydrothermal synthesis.